Clinical Profile of Patients Presenting with Acute Myocardial Infarction in United Arab Emirates: A Tertiary Care Center Government Hospital Experience - Sadeq Tabatabai; Nooshin Bazargani; Jasem Mohammed Al Hashmi (Dubai Medical Journal)
Background: Acute myocardial infarction (AMI) is one of the major causes of hospitalization and mortality worldwide. There has been limited data available to characterize AMI presentation, contemporary patterns of medical care, and outcomes in Dubai, United Arab Emirates. Methods: A single-center observational registry for patients with AMI was used. All patients admitted to Dubai Hospital with AMI (ST elevation and non-ST elevation) with positive troponin from the mid of August 2017 till the end of April 2018 were included in this registry. Clinical data, prior history, demographics, treatments, and outcomes were recorded from the patient’s electronic medical file of the hospital. Result: A total of 329 patients (male 92%, mean age 53.6 years) were included in our registry. The use of ambulance service was only 25%. Electrocardiogram findings of ST-segment elevation myocardial infarction (STEMI) were found in 57% and non-STEMI in 43%. History of prior ischemic heart disease was present in 21% of all cohort, diabetes in 36%, hypertension in 38%, and the current smoking rate was 35%. Reperfusion therapy was provided to 94% of the patients with STEMI; only 32% of them had primary angioplasty, and medical reperfusion was performed in 68%. One-third of them received thrombolysis within 30 min, and primary percutaneous coronary intervention (PCI) was provided to 38% within 90 min. All the patients received aspirin and adenosine diphosphate inhibitors within the first 24 h. The majority of the patients received other key medicines like beta-blocker, statin, and anticoagulant agents within 24 h. The in-hospital mortality rate was about 3%. Conclusions: Using data from the registry may provide an overview of the current status of AMI in Dubai. Medical reperfusion therapy is the most common reperfusion modality in our center, and this will raise the question of whether we need to launch a 24-h primary PCI program in our center.